Effect of resistance band and weight training on throwing velocity of club level baseball players in Sri Lanka - Priyadarshana, L.A.D.; Keerthirathne, M.G.S.S.; De Silva, L.H.K.P. (Faculty of Graduate Studies , University of Sri Jayewardenepura, 2021)
Throwing velocity is undoubtedly considered as one of the crucial factors that affects output of a baseball game .To improve throwing velocity, numerous training methods and approaches are being used .Therefore, the purpose of this study was to find the effect of the resistance band and weight training on throwing velocity of age (27±3),( mean ± SD )club level baseball players in Sri Lanka . Forty baseball players were recruited for the 8-week training program based on the inclusion criteria and availability of players .Initially, athletes were assigned into 3 groups :a control group (n=10), a weight training group (n=15), and a resistance band training group (n=15 .)The weight training group performed 6 upper body exercises by using barbells and dumbbells while the resistance band training group engaged in 6 upper body exercises with blue and red coloured bands. Moreover, the control group was only allowed to perform their daily routine baseball practices which were 3 days per week and 3 hours per day. Throwing velocity was measured by using a radar gun, and upper body strength was measured using the one-repetition maximum (1RM )bench press test to determine the relationship between strength and throwing velocity .Both test results were evaluated by using pre-test and posttests’ descriptive and inferential statistics .The weight training group and the resistance band group showed significant differences in 1RM bench press and the radar gun tests while the control group showed only a significant difference in the strength test .In addition, the control group revealed no significant difference in throwing velocity .Furthermore, the weight training group showed the greatest improvement in throwing velocity and 1RM bench press tests, and then the resistance band group followed the same .In conclusion, Strength training and resistance band training can be utilized to develop strength in the upper body and it may help to develop throwing velocity in other throwing sports, such as cricket, throw ball and so on.
Keywords: Throwing Velocity, Weight Training, Resistance-Band Training, Radar Gun Test, 1RM Bench Press Test